Intercultural Communication Issues in Small and Medium-Sized Foreign-Owned Companies in China - Wang, Jingxuan (My University, 2010)
Many small and medium-sized foreign-owned companies have been established in China due to its huge market and abolishment of entry restrictions in the tertiary industry in recent years. However, due to limited resources and lack of international experience, they have encountered more problems in performing effective communication with their overseas headquarters than big multinational corporations. The aim of this research is to develop a new model of the intercultural communication stages in these companies and to study what happens in these stages. Uncertainty/Anxiety Theory is used to explain that the stages could be regarded as a process in managing uncertainty and anxiety. The research also asks whether smaller cultural distance speeds up the process of going through the intercultural communication stages. Five interviews were made in this research to identify the intercultural communication stages which do exist in these companies and uncertainty declines as the stages revolve. It seems that cultural distance has some influence to the communication performance, but they could not be regarded as a decisive factor.
Keywords: small and medium-sized foreign-owned companies; intercultural communication; intercultural communication stages; Uncertainty/Anxiety Theory; cultural distance; fi=Viestintätieteet|en=Communication Studies|; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|